Advances in pathogenesis and treatment of vascular endothelial injury-related diseases mediated by mitochondrial abnormality - Pang, Boxian; Dong, Guangtong; Pang, Tieliang; Sun, Xinyao; Liu, Xin; Nie, Yifeng; Chang, Xing (Frontiers in Pharmacology, 2024)
Vascular endothelial cells, serving as a barrier between blood and the arterial wall, play a crucial role in the early stages of the development of atherosclerosis, cardiovascular diseases, and Alzheimer's disease. Mitochondria, known as the powerhouses of the cell, are not only involved in energy production but also regulate key biological processes in vascular endothelial cells, including redox signaling, cellular aging, calcium homeostasis, angiogenesis, apoptosis, and inflammatory responses. The mitochondrial quality control (MQC) system is essential for maintaining mitochondrial homeostasis. Current research indicates that mitochondrial dysfunction is a significant driver of endothelial injury and cardiovascular diseases. This article provides a comprehensive overview of the causes of endothelial injury in cardiovascular diseases, ischemic stroke in cerebrovascular diseases, and Alzheimer's disease, elucidating the roles and mechanisms of mitochondria in these conditions, and aims to develop more effective therapeutic strategies. Additionally, the article offers treatment strategies for cardiovascular and cerebrovascular diseases, including the use of clinical drugs, antioxidants, stem cell therapy, and specific polyphenols, providing new insights and methods for the clinical diagnosis and treatment of related vascular injuries to improve patient prognosis and quality of life. Future research should delve deeper into the molecular and mechanistic links between mitochondrial abnormalities and endothelial injury, and explore how to regulate mitochondrial function to prevent and treat cardiovascular diseases.